Return to sport following low-risk and high-risk bone stress injuries: a systematic review and meta-analysis. (31st January 2023) - Hoenig, Tim; Eissele, Julian; Strahl, André; Popp, Kristin L; Stürznickel, Julian; Ackerman, Kathryn E; Hollander, Karsten; Warden, Stuart J; Frosch, Karl-Heinz; Tenforde, Adam S; Rolvien, Tim
Abstract : Objective: Bone stress injuries (BSIs) are classified in clinical practice as being at low- or high-risk for complication based on the injury location. However, this dichotomous approach has not been sufficiently validated. The purpose of this systematic review was to examine the prognostic role of injury location on return-to-sport (RTS) and treatment complications after BSI of the lower extremity and pelvis. Design: Systematic review and meta-analysis. Data sources: PubMed, Web of Science, Cochrane CENTRAL and Google Scholar databases were searched from database inception to December 2021. Eligibility criteria for selecting studies: Peer-reviewed studies that reported site-specific RTS of BSIs in athletes. Results: Seventy-six studies reporting on 2974 BSIs were included. Sixteen studies compared multiple injury sites, and most of these studies (n=11) described the anatomical site of injury as being prognostic for RTS or the rate of treatment complication. Pooled data revealed the longest time to RTS for BSIs of the tarsal navicular (127 days; 95% CI 102 to 151 days) and femoral neck (107 days; 95% CI 79 to 135 days) and shortest duration of time for BSIs of the posteromedial tibial shaft (44 days, 95% CI 27 to 61 days) and fibula (56 days; 95% CI 13 to 100 days). Overall, more than 90% of athletes successfully returned to sport. Treatment complication rate was highest in BSIs of the femoral neck, tarsal navicular, anterior tibial shaft and fifth metatarsal; and lowest in the fibula, pubic bone and posteromedial tibial shaft. Conclusion: This systematic review supports that the anatomical site of BSIs influences RTS timelines and the risk of complication. BSIs of the femoral neck, anterior tibial shaft and tarsal navicular are associated with increased rates of complications and more challenging RTS. PROSPERO registration number: CRD42021232351.